Salt in matrix for thermochemical energy storage - A review. (2023) - Mohapatra, Dhammapada; Nandanavanam, Jalaiah
Abstract: Thermal energy storage (TES) method plays a vital role in storing and retrieving thermal energy from various sources (e.g. solar energy, industrial waste heat). Among all viable options for the TES, the reversible reaction pathway of thermochemical energy storage (TCES) has proved an experimentally much efficient form of energy storage over the latent and sensible energy storage. This review article focuses on a solid-gas system with water as sorbate for the TCES. At the material level, emphasis is put on comparing various pure thermochemical materials (TCMs) and salt in matrix (SIM), a thermochemical compound with porous material as a host. The basis of comparison among the compounds has been energy density and cyclic stability. It has been found that a pure TCM offers higher energy storage density compared to the SIM, while the latter exhibits better thermal cyclic stability. The porous host increases the surface area of the TCM leading to better mass and energy transfer and also prevents the deliquescence of the salt during the hydration process. This study also focuses on the synthesis of SIM, properties of host materials for SIM, and the use of various characterization methodologies for the analysis of SIM. [copyright information to be updated in production process]